Temperature effects on anionic/nonionic surfactant mixture and silica nanofluid dispersion for foam-EOR - Md Saad, N.A. (Elsevier Ltd, 2021)
Foam-assisted gas has been widely employed in enhanced oil recovery (EOR) by improving the volumetric sweep efficiency gas mobility of injected gas. However, the major obstacle of foam-assisted gas EOR is maintaining foam lamellaeâs stability, especially in harsh reservoir conditions. As mentioned above, the study focused on the effect of silica nanoparticles (SiO2 NPs) in an anionic/nonionic surfactant mixture in enhancing the stability of foam film. The optimum concentration of silica nanoparticles was determined through various experimental approaches. The surface tension and interfacial tension in the presence and absence of SiO2 NPs were measured and recorded. The Bartsch shaking method was applied to analyse the foam half-life and foam static stability. Anionic surfactant Sodium Dodecyl Sulfate (SDS) was utilised with the nonionic surfactant Triton X100 (TX100) at a ratio of 4:1. Addition of various concentration (0.2 wt, 0.4 wt, 0.6 wt, 0.8 wt and 1.0 wt) SiO2 NPs in two surfactant mixtures. The screening method was utilised to determine the optimum concentration of SiO2 NPs in SDS-TX100 surfactant mixture at 25 Â°C and 70 Â°C. The optimisation from the screening process demonstrated 0.4 wt SiO2 NPs was suitable in SDS-TX100 surfactant mixture for stabilising the foam films. Copyright Â© 2021 Elsevier Ltd. All rights reserved.